Elaboration of FAU-type zeolite beads with good mechanical performances for molecular decontamination. Issue 3 (4th January 2016) - Rioland, G.; Bullot, L.; Daou, T. J.; Simon-Masseron, A.; Chaplais, G.; Faye, D.; Fiani, E.; Patarin, J.
Abstract : FAU-type zeolite beads were formed through an shearer/mixer using organic binder (carboxymethylcellulose (CMC)) or inorganic binder (anhydrous sodium metasilicate (Na2 SiO3 )). Abstract : FAU-type zeolite beads were formed through an shearer/mixer using organic binder (carboxymethylcellulose (CMC)) or inorganic binder (anhydrous sodium metasilicate (Na2 SiO3 )). Mechanical and adsorption properties of these beads represent necessary characteristics for applications in molecular decontamination. The amount of binder and the size of beads were investigated to determine the optimum conditions to elaborate mechanically stable beads with high adsorption capacities. The size of beads varies from 0.25 mm to 2 mm and the amount of binder was tuned from 5 to 15 wt% of the total bead weight. Nitrogen adsorption–desorption measurements reveal no loss of micropore volume when 5 wt% of binder is used. Adsorption of pollutants were successfully carried out using n -hexane and 1, 2-dichlorobenzene as probe molecules. Indeed, FAU-type zeolite adsorbs 26 molecules of n -hexane and 29 molecules of 1, 2-dichlorobenzene per unit-cell, whereas the beads prepared with 5 wt% of CMC or Na2 SiO3 adsorb about 24 molecules of n -hexane and 25 molecules of 1, 2-dichlorobenzene per unit-cell, respectively. The mechanical performances are improved with the addition of only 5 wt% of binder in the mixture. Uniaxial compression tests show that the ultimate compressive strength was multiplied by 4 or 7 when only 5 wt% of CMC or sodium silicate are respectively involved for the conception of 1–2 mm zeolite beads.